Intercultural training and attitudes of physical education teachers towards immigrant students in Chile: A multi-stakeholder perspective - Bastian Carter-Thuillier; Víctor López-Pastor; Francisco Gallardo-Fuentes; Rodrigo Ramirez-Campillo; Cyntia del Río-Soto; Andrew Sortwell (Social Sciences and Humanities Open)
The number of immigrant students has significantly increased in Chile over the past decade; this has posed new challenges for teacher education in the field of Physical Education (PE), especially in the southern macrozone of the country, where there have historically been tensions related to the recognition of cultural diversity within schools. The present study was conducted in three university campuses in the southern macrozone of Chile. The study aimed to answer the following questions: (a) What are the attitudes towards immigrant K-12 students of pre-service PE teachers, their university professors and the PE teachers who guide their practicum experiences in the placement schools?; (b) What are the perceptions of immigrant K-12 students and their parents regarding the attitudes toward foreign pupils of pre-service (who undergo practicum experience in schools) and PE in-service school teachers (who guide and give feedback on the practicum)?; (c) What are the differences and similarities between the perceptions of all stakeholders (PE in-service and pre-service teachers, their professors, immigrant K-12 students and their parents) about the effectiveness and appropriateness of university strategies preparing future PE teachers to engage with in intercultural contexts? University professors, pre-service PE teachers, and in-service PE teachers display positive attitudes towards interculturality, defined as the presence of K-12 immigrant students in schools. However, significative differences in attitudes exist between those responsible for their teacher education (university professors and in-service PE school teachers). Some K-12 immigrant students and their parents hold a critical perspective toward in-service PE school teachers (both pre-service and in-service), primarily because they perceive a lack of cultural inclusion within the classroom. There is a consensus among the majority of participants regarding the necessity to enhance teacher education concerning interculturality.